RANCANG BANGUN SISTEM INFORMASI MONITORING PELANGGARAN TATA TERTIB SISWA BERBASIS WEB - Safitri, Widia; Sarmidi; Habibie, Alfadl (PRODUKTIF : Jurnal Ilmiah Pendidikan Teknologi Informasi, 2024)
This study aims to design and develop a web-based student discipline violation monitoring information system at SMK Islam Kawalu, as well as evaluate its feasibility. The research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The design is carried out using Unified Modeling Language (UML), and the system is developed using PHP programming language. The results show that the system is deemed "feasible" based on evaluations from experts, administrative staff, guidance counselors, and class teachers. Student evaluations also indicate a "very good" rating. This system facilitates the recording, management, and reporting of violation data in an integrated manner, providing an effective solution to support student discipline enforcement. Further development is recommended, including the addition of data backup features, deletion of data for specific periods, and an enhanced user interface to make it more attractive and functional.